Headache Characteristic in Brain Tumor Patients - Sembiring, Saulina; Sofyan, Henry Riyanto; Madjid, Irma Savitri; Alvonsius Silalahi, Raymond Aris Nimrod; Albertin, Elizabeth; Aninditha, Tiara (Indonesian Journal of Cancer, 2025)
Background: Headache is an alarm for structural abnormalities, and it frequently manifests as an initial symptom of brain tumors, with an occurrence rate ranging between 36-80%, depending on the type and location of the tumorMethods: We conducted a retrospective cross-sectional study to observe hospitalized brain tumor patients at Dr. Cipto Mangunkusumo Hospital from January 2022 to March 2023. This study described the prevalence and the percentages of baseline characteristics.Results: Our study revealed that out of 101 brain tumor patients, predominated by females (60.4%) with a mean age of 46.2 years. Secondary brain tumors originating from breast cancer were more prevalent (13.9%). Frontal lobe location was frequent (32.3%), displaying rapid growth (66.3%), focal deficits (82.2%), and headaches (79.2%). Atypical headache was the most common phenotype (40%), often occurring either before the onset of neurological deficits (prechronous) or concurrently with them (synchronous). Discussion: The study revealed that high-grade, rapidly growing brain tumors tend to induce focal neurological deficits and headaches due to the tumor’s progressivity and mass effect. Brain tumor lesions were primarily found in the frontal lobe of the supratentorial region, displaying a mainly atypical headache phenotype. The absence of pain receptors in the parenchyma suggested that pain resulted from mechanical stimulation of other pain-sensitive structures.Conclusion: Atypical headaches occurring within 30 days before neurological deficits could indicate potential malignancy.